Management of a rare fifth metatarsal exostosis with pseudoarthrosis in a 29-year-old male - Banal, Jatin; Chakrabarti , Dip (International Journal of Research in Orthopaedics, 2025)
Exostoses of the fifth metatarsal are uncommon, and their association with pseudoarthrosis is exceptionally rare. Such lesions can lead to chronic pain and functional impairment, often delaying diagnosis. Authors report the case of a 29-year-old male with longstanding lateral foot pain unresponsive to conservative treatment. Radiographic evaluation revealed a fifth metatarsal exostosis with pseudoarthrosis. Surgical excision and debridement were performed, with preoperative evaluation and planning aided by 3D bone models to better define the lesion and optimize the approach. Postoperatively, the patient experienced significant improvement in pain and function, achieving full return to normal activities and work. This case highlights the need to consider unusual bony pathologies in patients with persistent lateral foot pain.